An Acute Flaccid Paralysis Surveillance–Based Serosurvey of Poliovirus Antibodies in Western Uttar Pradesh, India. (1st November 2014) - Bahl, Sunil; Gary, Howard E.; Jafari, Hamid; Sarkar, Bidyut K.; Pathyarch, Surendra K.; Sethi, Raman; Deshpande, Jagadish
Abstract : Background. Despite intensified use of monovalent oral poliovirus type 1 vaccine and improved coverage of immunization campaigns, wild poliovirus type 1 persisted in Indian states of Uttar Pradesh and Bihar during 2006 to 2009. Methods. A serosurvey was conducted among cases of acute flaccid paralysis in the 25 high-polio-incidence districts of western Uttar Pradesh. Children were recruited by age group (6–11 months, 12–24 months, and 25–69 months) from among cases reported through the acute flaccid paralysis surveillance system between November 2008 and August 2009. Results. Seroprevalence for type 1 wild poliovirus was >96.4% for each age group. The seroprevalence of wild poliovirus types 2 and 3 increased with age, from 36.7% to 73.4% for type 2 and from 39.0% to 74.1% for type 3. In addition to the number of type-specific vaccine doses, father's level of education, being from a Muslim family, height for age, and female sex were the socioeconomic risk factors associated with seronegativity to poliovirus. Conclusions. The seroprevalence and risk factors identified in this study were consistent with the epidemiology of polio, and the findings were instrumental in optimizing vaccination strategy in western Uttar Pradesh with respect to the choice of OPV types, the frequency of supplementary immunization campaigns, and the urgency to improve routine immunization services.